Blue nevus of the nail: A case report and review. Issue 4 (16th July 2020) - Satolli, Francesca; Gandolfi, Marco; Rovesti, Miriam; Zucchi, Alfredo; Roberta, Manuguerra; Stanganelli, Ignazio; De Felici Del Giudice, Mariabeatrice; Torello, Lotti; Feliciani, Claudio
Abstract: Blue nevus (BN), in all its clinical variants, rarely affects the nail bed. This leads to difficulty in the diagnosis of BN within the nail bed as well as to challenges with regard to its treatment and follow‐up management, not solely attributed to the intrinsic difficulty of the anatomical site. We present the first case in the literature of an acquired cellular BN entirely confined within the nail bed, in a female Caucasian patient. We propose diagnostic and therapeutic options based on personal clinical and surgical experience.